BNT-based leadless piezoelectric ceramic and preparation method thereof

By introducing NdAlO3 and LiTaO3 into BNT-based lead-free piezoelectric ceramics, and doping them with Zn, Mg, Cu and V ions, and optimizing the sintering process, the piezoelectric properties were improved and the application range was broadened.

CN119263819AInactive Publication Date: 2025-01-07HUNAN MEICHENG NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411796033.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing BNT-based lead-free piezoelectric ceramics have good but not yet optimal piezoelectric properties, which limits their application potential in pressure sensors, acceleration sensors, and acoustic sensors.

Method used

By introducing NdAlO3 and LiTaO3 with perovskite structures into BNT-based lead-free piezoelectric ceramics to form a multi-component solid solution, and doping with ions of divalent metal elements Zn, Mg, Cu and V, the (M1/3V2/3)4+ composite ions were designed to modify the BNT ceramics, and the sintering process was optimized to improve the piezoelectric properties.

Benefits of technology

This significantly improves the piezoelectric properties of BNT-based lead-free piezoelectric ceramics, making them promising for applications in pressure sensors, accelerometers, and acoustic sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263819A_ABST
    Figure CN119263819A_ABST
Patent Text Reader

Abstract

The invention relates to the field of piezoelectric ceramic materials, in particular to BNT-based leadless piezoelectric ceramic and a preparation method thereof.The BNT-based leadless piezoelectric ceramic has the chemical structural general formula as follows: (1-y-z) Bi1 / 2Na1 / 2Ti1-x (M1 / 3V2 / 3) xO3-yNdAlO3-zLiTaO3, M is a divalent metal element, x is larger than 0 and smaller than or equal to 0.015, y is larger than or equal to 0.01 and smaller than or equal to 0.05, z is larger than or equal to 0.01 and smaller than or equal to 0.05, and it can be known through tests that the BNT-based leadless piezoelectric ceramic prepared through the method has excellent piezoelectric performance and can be applied to the field of piezoelectric ceramics. The method has wide application prospects in the fields of pressure sensors, acceleration sensors, sonic sensors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of piezoelectric ceramic materials, in particular to a BNT-based lead-free piezoelectric ceramic and a preparation method thereof. Background Art

[0002] Sodium bismuth titanate (Ba 0.5 Na 0.5 TiO3, BNT) is a ferroelectric with a perovskite structure with A-site ions consisting of Na + and Bi 3+ in a 1:1 ratio, and the B site ion is occupied by Ti 4+ It has relatively good piezoelectric properties, a piezoelectric constant of about 73pC / N, and a high Curie temperature of 320°C. It is considered to be the most likely lead-free piezoelectric ceramic system to replace lead-based piezoelectric ceramics. How to further improve its piezoelectric properties and broaden its application scenarios has become a current research hotspot. Summary of the invention

[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a BNT-based lead-free piezoelectric ceramic and a preparation method thereof.

[0004] The technical solutions adopted are as follows: A BNT-based lead-free piezoelectric ceramic, the general chemical structure of which is shown below: (1-yz)Bi 1 / 2 Na 1 / 2 Ti 1-x (M 1 / 3 V 2 / 3 ) x O3-yNdAlO3-zLiTaO3 Wherein, M is any one of Zn, Mg, and Cu, 0<x≤0.015, 0.01≤y≤0.05, 0.01≤z≤0.05.

[0005] Further, 0.006≤x≤0.012, 0.02≤y≤0.04, 0.02≤z≤0.04.

[0006] Furthermore, x may be 0.006, 0.007, 0.008, 0.009, 0.01, 0.011, 0.012, which are merely for ease of understanding and are not intended to be limiting. Furthermore, y may be 0.02, 0.021, 0.022, 0.023, 0.024, 0.025, 0.026, 0.027, 0.028, 0.029, 0.03, 0.031, 0.032, 0.033, 0.034, 0.035, 0.036, 0.037, 0.038, 0.039, 0.04, which are merely for the convenience of understanding and are not intended to be limiting; Furthermore, z can be 0.02, 0.021, 0.022, 0.023, 0.024, 0.025, 0.026, 0.027, 0.028, 0.029, 0.03, 0.031, 0.032, 0.033, 0.034, 0.035, 0.036, 0.037, 0.038, 0.039, 0.04, which are only for the convenience of understanding and are not intended to be limiting; Further, x=0.01.

[0007] Further, y=0.03.

[0008] Further, z=0.02.

[0009] The present invention also provides a method for preparing a BNT-based lead-free piezoelectric ceramic: Mix Bi2O3, Na2CO3, TiO2, M oxide and V2O5, ball-mill and dry, pre-sinter at 850-950℃ for 1-5h to obtain a first mixed powder, then mix the first mixed powder with Nd2O3, Al2O3, Li2CO3 and Ta2O3, ball-mill and dry to obtain a second mixed powder, granulate the second mixed powder, sieve and press into a green body, heat the green body to 550-650℃ in one stage, keep it for 1-3h to debind, and then heat it to 1200-1300℃ in a second stage and sinter it for 1-3h.

[0010] Furthermore, the preparation method of the above-mentioned BNT-based lead-free piezoelectric ceramic is as follows: Bi2O3, Na2CO3, TiO2, M oxide, and V2O5 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, the ball milling speed is 300 r / min, and the forward and reverse alternating ball milling is adopted, the interval time is 1h, and the total ball milling time is 10h. After the mixed material obtained by ball milling is dried, it is pre-calcined at 850-950℃ for 1-5h to obtain a first mixed powder, and then the first mixed powder and Nd2O3, Al2O3, Li2CO3, and Ta2O3 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, and the ball milling speed is 300 r / min, adopt forward and reverse alternating ball milling, the interval time is 1h, the total ball milling time is 10h, the mixed material obtained by ball milling is dried to obtain the second mixed powder, the binder is added to the second mixed powder to granulate, the obtained granules are passed through an 80-mesh sieve and poured into a mold and pressed into a green body, the green body is first kept at 550-650℃ for debinding for 1-3h, and then heated to 1200-1300℃ for sintering for 1-3h in a second stage.

[0011] Furthermore, during granulation, a PVA solution with a mass fraction of 3-8% is used as a binder.

[0012] Furthermore, the pressure during compression molding is 100-200 MPa.

[0013] Furthermore, the heating rate in the first stage of heating is 1-3°C / min, and the heating rate in the second stage of heating is 5-15°C / min.

[0014] Beneficial effects of the present invention: The present invention provides a BNT-based lead-free piezoelectric ceramic, wherein the ionic radius of divalent metal elements Zn, Mg, Cu and V is similar to that of Ti. 4+ (0.0605nm) is relatively close, therefore, the present invention combines the advantages of the two ions and designs (M 1 / 3 V 2 / 3 ) 4+ The composite ions were used to dope BNT ceramics and achieved good technical results. The prepared BNT-based lead-free piezoelectric ceramics have excellent piezoelectric properties. In addition, in order to improve the piezoelectric properties of BNT-based ceramic materials and make them have practical application significance, the present invention introduces NdAlO3 and LiTaO3 with a perovskite structure into BNT-based lead-free piezoelectric ceramics to form a multi-component solid solution with a quasi-modular phase boundary. Near the quasi-modular phase boundary component, the spontaneous polarization of the BNT-based lead-free piezoelectric ceramics becomes easier to change direction under the action of an external electric field or stress, and the piezoelectric performance is greatly improved. The test shows that the BNT-based lead-free piezoelectric ceramics prepared by the present invention have excellent piezoelectric properties and have broad application prospects in the fields of pressure sensors, acceleration sensors, acoustic wave sensors, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is the SEM image of the lead-free piezoelectric ceramic prepared in Example 1. DETAILED DESCRIPTION

[0016] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0017] Embodiment 1: This embodiment provides a BNT-based lead-free piezoelectric ceramic, the general chemical structure of which is shown below: 0.95Bi 1 / 2 Na 1 / 2 Ti 0.09 (Cu 1 / 3 V 2 / 3 ) 0.01 O3-0.03NdAlO3-0.02LiTaO3 Preparation method of the above-mentioned BNT-based lead-free piezoelectric ceramic: Bi2O3, Na2CO3, TiO2, CuO and V2O5 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, the ball milling speed is 300r / min, and the forward and reverse alternating ball milling is adopted, the interval time is 1h, and the total ball milling time is 10h. After the mixed material obtained by ball milling is dried, it is pre-calcined at 850℃ for 2h to obtain a first mixed powder, and then the first mixed powder and Nd2O3, Al2O3, Li2CO3 and Ta2O3 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, and the ball milling speed is 300 r / min, and adopted positive and reverse alternating ball milling with an interval time of 1h and a total ball milling time of 10h. The mixed material obtained by ball milling was dried to obtain a second mixed powder, and a PVA solution with a mass fraction of 5% was added to the second mixed powder as a binder for granulation. The obtained granules were passed through an 80-mesh sieve and poured into a mold, and pressed into a green body under a pressure of 100MPa. The green body was first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2h for debinding, and then heated to 1250℃ at a heating rate of 10℃ / min in a second stage and sintered for 2h.

[0018] Embodiment 2: This embodiment provides a BNT-based lead-free piezoelectric ceramic, the general chemical structure of which is shown below: 0.95Bi 1 / 2 Na 1 / 2 Ti 0.09 (Mg 1 / 3 V 2 / 3 ) 0.01 O3-0.03NdAlO3-0.02LiTaO3 Preparation method of the above-mentioned BNT-based lead-free piezoelectric ceramic: Bi2O3, Na2CO3, TiO2, MgO and V2O5 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, the ball milling speed is 300r / min, and the forward and reverse alternating ball milling is adopted, the interval time is 1h, and the total ball milling time is 10h. After the mixed material obtained by ball milling is dried, it is pre-calcined at 850℃ for 2h to obtain a first mixed powder, and then the first mixed powder and Nd2O3, Al2O3, Li2CO3 and Ta2O3 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, and the ball milling speed is 300 r / min, and adopted positive and reverse alternating ball milling with an interval time of 1h and a total ball milling time of 10h. The mixed material obtained by ball milling was dried to obtain a second mixed powder, and a PVA solution with a mass fraction of 5% was added to the second mixed powder as a binder for granulation. The obtained granules were passed through an 80-mesh sieve and poured into a mold, and pressed into a green body under a pressure of 100MPa. The green body was first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2h for debinding, and then heated to 1250℃ at a heating rate of 10℃ / min in a second stage and sintered for 2h.

[0019] Embodiment 3: This embodiment provides a BNT-based lead-free piezoelectric ceramic, the general chemical structure of which is shown below: 0.95Bi 1 / 2 Na 1 / 2 Ti 0.09 (Zn 1 / 3 V 2 / 3 ) 0.01 O3-0.03NdAlO3-0.02LiTaO3 Preparation method of the above-mentioned BNT-based lead-free piezoelectric ceramic: Bi2O3, Na2CO3, TiO2, ZnO and V2O5 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, the ball milling speed is 300r / min, and the forward and reverse alternating ball milling is adopted, the interval time is 1h, and the total ball milling time is 10h. After the mixed material obtained by ball milling is dried, it is pre-calcined at 850℃ for 2h to obtain a first mixed powder, and then the first mixed powder and Nd2O3, Al2O3, Li2CO3 and Ta2O3 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, and the ball milling speed is 300 r / min, and adopted positive and reverse alternating ball milling with an interval time of 1h and a total ball milling time of 10h. The mixed material obtained by ball milling was dried to obtain a second mixed powder, and a PVA solution with a mass fraction of 5% was added to the second mixed powder as a binder for granulation. The obtained granules were passed through an 80-mesh sieve and poured into a mold, and pressed into a green body under a pressure of 100MPa. The green body was first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2h for debinding, and then heated to 1250℃ at a heating rate of 10℃ / min in a second stage and sintered for 2h.

[0020] Embodiment 4: This embodiment provides a BNT-based lead-free piezoelectric ceramic, the general chemical structure of which is shown below: 0.95Bi 1 / 2 Na 1 / 2 Ti 0.09 (Cu 1 / 3 V 2 / 3 ) 0.01 O3-0.03NdAlO3-0.02LiTaO3 Preparation method of the above-mentioned BNT-based lead-free piezoelectric ceramic: Bi2O3, Na2CO3, TiO2, CuO and V2O5 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, the ball milling speed is 300r / min, and the forward and reverse alternating ball milling is adopted, the interval time is 1h, and the total ball milling time is 10h. After the mixed material obtained by ball milling is dried, it is pre-calcined at 850℃ for 2h to obtain a first mixed powder, and then the first mixed powder and Nd2O3, Al2O3, Li2CO3 and Ta2O3 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, and the ball milling speed is 300 r / min, using forward and reverse alternating ball milling, the interval time is 1h, the total ball milling time is 10h, the mixed material obtained by ball milling is dried to obtain the second mixed powder, 5% by mass fraction of PVA solution is added to the second mixed powder as a binder for granulation, the obtained granules are passed through an 80-mesh sieve and poured into a mold, and pressed into a green body under a pressure of 100MPa, the green body is first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2h to debind, and then heated to 1200℃ at a heating rate of 10℃ / min in two stages and sintered for 2h.

[0021] Embodiment 5: This embodiment provides a BNT-based lead-free piezoelectric ceramic, the general chemical structure of which is shown below: 0.95Bi 1 / 2 Na 1 / 2 Ti 0.09 (Cu 1 / 3 V 2 / 3 ) 0.01 O3-0.03NdAlO3-0.02LiTaO3 Preparation method of the above-mentioned BNT-based lead-free piezoelectric ceramic: Bi2O3, Na2CO3, TiO2, CuO and V2O5 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, the ball milling speed is 300r / min, and the forward and reverse alternating ball milling is adopted, the interval time is 1h, and the total ball milling time is 10h. After the mixed material obtained by ball milling is dried, it is pre-calcined at 850℃ for 2h to obtain a first mixed powder, and then the first mixed powder and Nd2O3, Al2O3, Li2CO3 and Ta2O3 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, and the ball milling speed is 300 r / min, using forward and reverse alternating ball milling with an interval of 1h and a total ball milling time of 10h. The mixed material obtained by ball milling is dried to obtain a second mixed powder. A PVA solution with a mass fraction of 5% is added to the second mixed powder as a binder for granulation. The obtained granules are passed through an 80-mesh sieve and poured into a mold, and pressed into a green body under a pressure of 100MPa. The green body is first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2h to debind, and then heated to 1300℃ at a heating rate of 10℃ / min in a second stage and sintered for 2h.

[0022] Comparative Example 1: It is basically the same as Example 1, except that (Cu 1 / 3 V 2 / 3 ) 4+ doping; This comparative example provides a BNT-based lead-free piezoelectric ceramic, the general chemical structure of which is shown below: 0.95Bi 1 / 2 Na 1 / 2 TiO3-0.03NdAlO3-0.02LiTaO3 Preparation method of the above-mentioned BNT-based lead-free piezoelectric ceramic: Bi2O3, Na2CO3 and TiO2 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, the ball milling speed is 300 r / min, and the forward and reverse alternating ball mill is adopted, the interval time is 1h, and the total ball milling time is 10h. After the mixed material obtained by ball milling is dried, it is pre-calcined at 850℃ for 2h to obtain a first mixed powder, and then the first mixed powder and Nd2O3, Al2O3, Li2CO3 and Ta2O3 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, and the ball milling speed is 300 r / min, and adopted positive and reverse alternating ball milling with an interval time of 1h and a total ball milling time of 10h. The mixed material obtained by ball milling was dried to obtain a second mixed powder, and a PVA solution with a mass fraction of 5% was added to the second mixed powder as a binder for granulation. The obtained granules were passed through an 80-mesh sieve and poured into a mold, and pressed into a green body under a pressure of 100MPa. The green body was first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2h for debinding, and then heated to 1250℃ at a heating rate of 10℃ / min in a second stage and sintered for 2h.

[0023] Comparative Example 2: The same as Example 1, except that NdAlO3 is used instead of LiTaO3; This comparative example provides a BNT-based lead-free piezoelectric ceramic, the general chemical structure of which is shown below: 0.95Bi 1 / 2 Na 1 / 2 Ti 0.09 (Cu 1 / 3 V 2 / 3 ) 0.01 O3-0.05NdAlO3 Preparation method of the above-mentioned BNT-based lead-free piezoelectric ceramic: Bi2O3, Na2CO3, TiO2, CuO and V2O5 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon can, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, the ball milling speed is 300r / min, and the forward and reverse alternating ball milling is adopted, the interval time is 1h, and the total ball milling time is 10h. After the mixed material obtained by ball milling is dried, it is pre-calcined at 850℃ for 2h to obtain a first mixed powder, and then the first mixed powder is poured into a ball mill with Nd2O3 and Al2O3 for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon can, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, and the ball milling speed is 300 r / min, and adopted positive and reverse alternating ball milling with an interval time of 1h and a total ball milling time of 10h. The mixed material obtained by ball milling was dried to obtain a second mixed powder, and a PVA solution with a mass fraction of 5% was added to the second mixed powder as a binder for granulation. The obtained granules were passed through an 80-mesh sieve and poured into a mold, and pressed into a green body under a pressure of 100MPa. The green body was first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2h for debinding, and then heated to 1250℃ at a heating rate of 10℃ / min in a second stage and sintered for 2h.

[0024] Comparative Example 3: The method is substantially the same as Example 1, except that LiTaO3 is used instead of NdAlO3; This comparative example provides a BNT-based lead-free piezoelectric ceramic, the general chemical structure of which is shown below: 0.95Bi 1 / 2 Na 1 / 2 Ti 0.09 (Cu 1 / 3 V 2 / 3 ) 0.01 O3-0.05LiTaO3 Preparation method of the above-mentioned BNT-based lead-free piezoelectric ceramic: Bi2O3, Na2CO3, TiO2, CuO and V2O5 are poured into a ball mill for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, the ball milling speed is 300r / min, and the forward and reverse alternating ball milling is adopted, the interval time is 1h, and the total ball milling time is 10h. After the mixed material obtained by ball milling is dried, it is pre-calcined at 850℃ for 2h to obtain a first mixed powder, and then the first mixed powder is poured into a ball mill with Li2CO3 and Ta2O3 for ball milling and mixing, wherein the ball mill is a planetary ball mill, the ball mill adopts a nylon jar, the ball milling balls are zirconia balls, the ball milling medium is anhydrous ethanol, and the ball milling speed is 300 r / min, and adopted positive and reverse alternating ball milling with an interval time of 1h and a total ball milling time of 10h. The mixed material obtained by ball milling was dried to obtain a second mixed powder, and a PVA solution with a mass fraction of 5% was added to the second mixed powder as a binder for granulation. The obtained granules were passed through an 80-mesh sieve and poured into a mold, and pressed into a green body under a pressure of 100MPa. The green body was first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2h for debinding, and then heated to 1250℃ at a heating rate of 10℃ / min in a second stage and sintered for 2h.

[0025] Performance Testing: The surfaces of the BNT-based lead-free piezoelectric ceramics prepared in Examples 1-5 and Comparative Examples 1-3 were polished, coated with silver paste on both sides, kept at 750°C for 10 min, and finally polarized at a DC voltage of 4 kV / mm for 20 min in silicone oil at 120°C and placed for 24 h as samples to test their electrical properties.

[0026] The room temperature piezoelectric constant of the sample was measured using a ZJ-3AN quasi-static piezoelectric constant tester. The electromechanical coupling coefficient kp, mechanical quality factor Qm and dielectric loss tanδ (25°C, 1V, 1kHz) of the samples were measured and analyzed using a precision impedance analyzer (Agilent HP4294A). The test results are shown in Table 1 below: ; As can be seen from Table 1 above, the BNT-based lead-free piezoelectric ceramics prepared in the present invention have excellent piezoelectric properties; It can be seen from the comparison of Examples 1-3 that when M is any one of Zn, Mg, and Cu, the prepared BNT-based lead-free piezoelectric ceramics have relatively excellent piezoelectric properties; It can be seen from the comparison between Example 1 and Examples 4 and 5 that different sintering temperatures will affect the piezoelectric properties of the prepared BNT-based lead-free piezoelectric ceramics, and the piezoelectric properties of the prepared BNT-based lead-free piezoelectric ceramics are optimal when the sintering temperature is 1250°C. It can be seen from the comparison between Example 1 and Comparative Example 1 that (Cu 1 / 3 V 2 / 3 ) 4+ Doping has a positive effect on improving the piezoelectric properties of the prepared BNT-based lead-free piezoelectric ceramics; By comparing Example 1 with Comparative Examples 2 and 3, it can be seen that the addition of LiTaO3 and NdAlO3 has a positive effect on the improvement of the piezoelectric properties of the prepared BNT-based lead-free piezoelectric ceramics.

[0027] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A BNT-based lead-free piezoelectric ceramic, characterized in that: Its chemical structure is shown below: <h2 style=";text-align:left;direction:ltr">(1-yz)Bi<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> Na<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> (M<h2 style=";text-align:left;direction:ltr"> 1 / 3 <h2 style=";text-align:left;direction:ltr"> V<h2 style=";text-align:left;direction:ltr"> 2 / 3 <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> O3-yNdAlO3-zLiTaO3 Wherein, M is any one of Zn, Mg, and Cu, 0<x≤0.015, 0.01≤y≤0.05, 0.01≤z≤0.

05.

2. The BNT-based lead-free piezoelectric ceramic according to claim 1, characterized in that: 0.006≤x≤0.012, 0.02≤y≤0.04, 0.02≤z≤0.

04.

3. The BNT-based lead-free piezoelectric ceramic according to claim 1, characterized in that: x=0.01。 4. The BNT-based lead-free piezoelectric ceramic according to claim 1, characterized in that: y=0.03。 5. The BNT-based lead-free piezoelectric ceramic according to claim 1, characterized in that: z=0.02。 6. A method for preparing a BNT-based lead-free piezoelectric ceramic according to any one of claims 1 to 5, characterized in that: Mix Bi2O3, Na2CO3, TiO2, M oxide and V2O5, ball-mill and dry, pre-sinter at 850-950℃ for 1-5h to obtain a first mixed powder, then mix the first mixed powder with Nd2O3, Al2O3, Li2CO3 and Ta2O3, ball-mill and dry to obtain a second mixed powder, granulate the second mixed powder, sieve and press into a green body, heat the green body to 550-650℃ in one stage, keep it for 1-3h to debind, and then heat it to 1200-1300℃ in a second stage and sinter it for 1-3h.

7. The method for preparing the BNT-based lead-free piezoelectric ceramic according to claim 6, characterized in that: During granulation, a PVA solution with a mass fraction of 3-8% is used as a binder.

8. The method for preparing the BNT-based lead-free piezoelectric ceramic according to claim 6, characterized in that: The pressure during compression molding is 100-200MPa.

9. The method for preparing the BNT-based lead-free piezoelectric ceramic according to claim 6, characterized in that: The heating rate during the first stage of heating is 1-3°C / min, and the heating rate during the second stage of heating is 5-15°C / min.

Citation Information

Cited By

  • Composite high-temperature piezoelectric ceramic material and preparation method thereof

    CN119462132A